Titanium Disulfide Coated Carbon Nanotube Hybrid Electrodes Enable High Energy Density Symmetric Pseudocapacitors. Issue 5 (11th December 2017) - Zang, Xining; Shen, Caiwei; Kao, Emmeline; Warren, Roseanne; Zhang, Ruopeng; Teh, Kwok Siong; Zhong, Junwen; Wei, Minsong; Li, Buxuan; Chu, Yao; Sanghadasa, Mohan; Schwartzberg, Adam; et al.
Abstract: While electrochemical supercapacitors often show high power density and long operation lifetimes, they are plagued by limited energy density. Pseudocapacitive materials, in contrast, operate by fast surface redox reactions and are shown to enhance energy storage of supercapacitors. Furthermore, several reported systems exhibit high capacitance but restricted electrochemical voltage windows, usually no more than 1 V in aqueous electrolytes. Here, it is demonstrated that vertically aligned carbon nanotubes (VACNTs) with uniformly coated, pseudocapacitive titanium disulfide (TiS2 ) composite electrodes can extend the stable working range to over 3 V to achieve a high capacitance of 195 F g −1 in an Li‐rich electrolyte. A symmetric cell demonstrates an energy density of 60.9 Wh kg −1 —the highest among symmetric pseudocapacitors using metal oxides, conducting polymers, 2D transition metal carbides (MXene), and other transition metal dichalcogenides. Nanostructures prepared by an atomic layer deposition/sulfurization process facilitate ion transportation and surface reactions to result in a high power density of 1250 W kg −1 with stable operation over 10 000 cycles. A flexible solid‐state supercapacitor prepared by transferring the TiS2 –VACNT composite film onto Kapton tape is demonstrated to power a 2.2 V light emitting diode (LED) for 1 min. Abstract : TiS2 is coated coaxially onto vertically aligned carbon nanotubes (VACNTs) via an atomic layer deposition sulfurization process, providing an exceptionally high capacitance of 195 F g ‐1 and working voltage window up to 3 V in a Li + ion rich (21 m) electrolyte. The energy density of a supercapacitor based on TiS2 –VACNT electrodes is enhanced to 60.9 Wh kg ‐1, which outperforms many other pseudocapacitors.